Review of software applications for agricultural production in Croatia - Brezinščak, Luka; Mesić, Milan, agronom (2019)
The application of mobile devices (smartphones, tablets, etc.) to the agriculture sector has been greatly increased in the last decade. The ICT technologies have become an essential part of any business. Using Internet on mobile devices can prove to be essential in agriculture production. A new generation of mobile devices are lower in price and more user-friendly. This paper provides an overview of software applications that are created in Croatia and are mostly in the Croatian language. They are divided into groups of agriculture related applications; agriculture management information apps; agriculture information resource apps; agriculture calculator apps; agriculture news apps, weather apps. The research shows the agri-apps are still in its infancy and we can say that it reflects the state of agriculture in Croatia. Apps are a promising solution for farmers enabling them quick and trustworthy access to information. At the moment, further analyses are needed for scientific proof and improvement of a product.
Primjena mobilnih uređaja (smartphona, tableta, itd.) u sektoru poljoprivrede se uvelike povećala u posljednjih deset godina. Informacijskokomunikacijske tehnologije (ICT) su postale važan dio u svakom poslu.Korištenje Interneta na mobilnim uređajima može se pokazati kao ključno u donošenju odluka u poljoprivrednoj proizvodnji. Nova generacija mobilnih uređaja postiže niže cijene i više je "user-friendly". U radu se daje pregled softverskih aplikacija na hrvatskom jeziku načinjenih u Hrvatskoj. One su podijeljene u skupine poljoprivrednih aplikacija; aplikacije za upravljanje poljoprivrednom proizvodnjom; aplikacije za dokumentiranje u poljoprivredi; aplikacije za poljoprivredne kalkulacije; vijesti iz poljoprivrede; vremenske prognoze; informacije iz državnih poljoprivrednih institucija. Istraživanje pokazuje da su poljoprivredne aplikacije još uvijek u povojima i možemo reći da one odražavaju stanje poljoprivrede u Hrvatskoj. Aplikacije su obećavajuće rješenje za poljoprivrednike omogućujući im brz i pouzdan pristup informacijama. U ovom trenutku, potrebne su daljnje analize kako bi se znanstveno dokazala pouzdanost dostupnih aplikacija.
Bibliografija: 32 jed.
Abstract ; Sažetak.
Keywords: Mobilne aplikacije -- Mobilni uređaji -- Poljoprivredna proizvodnja; Hrvatska